Classificação dos solos e rochas sedimentares da região de Santa Maria/RS segundo a metodologia MCT - Damo, Taiana Poerschke (2016)
This research aimed to classify soils from the region of Santa Maria, in the state of Rio Grande do Sul, according to the MCT Methodology, seeking to know the peculiarities of the tropical soils of the region. The methodology applied in this study consisted in situate, collect and characterization of the soil deposits, and the conduction of laboratory tests. It was chosen two typical soil profiles from the geotechnical units of the region and two materials from deposits inside the studied area. Through laboratory tests, materials were classified according to the traditional systems of geotechnical classification, USCS and TRB, which are based in regulations from United States and Europe, temperate climate regions, and are substantiated in the value of consistence limit and soil granulometry. Besides the physical, chemical and mechanical characterization, it was performed triaxial tests with repeated loads to obtain the resilience modulus and resilient classification of the studied soils. The experiments of the MCT, MCT-M and Tablets Method were performed to understand the behavior of the soils, in view of the subtropical climate in the state and the presence of lateritic soils. Thus, it is possible to compare the classification methods, verifying the deficiency in the traditional methods related to lateritic soils and prove the validity of the Tablets Method as a simplified form to soils characterization. The results of this research show that MCT Methodology, developed to tropical soils, is an important tool to make feasible projects of low traffic pavements, minimizing costs and optimizing the use of tropical soils in these enterprises.